Dimethyl ether electro-oxidation on platinum surfaces. (November 2016) - Roling, Luke T.; Herron, Jeffrey A.; Budiman, Winny; Ferrin, Peter; Mavrikakis, Manos
Abstract: A first-principles density functional theory study was performed to elucidate the mechanism of dimethyl ether electro-oxidation on three low-index platinum surfaces (Pt(111), Pt(100), and Pt(211)). The goal of this study is to provide a fundamental explanation for the high activity observed experimentally on Pt(100) compared to Pt(111) and stepped surfaces. We determine that the enhanced activity of Pt(100) stems from more facile C–O bond breaking kinetics, as well as from easier removal of CO as a surface poison through activation of water. In general, the C–O bond (in CH x OCH y ) becomes easier to break as dimethyl ether is dehydrogenated to a greater extent. In contrast, dehydrogenation becomes more difficult as more hydrogen atoms are removed. We perform two analyses of probable reaction pathways, which both identify CHOC and CO as the key reaction intermediates on these Pt surfaces. We show that the reaction mechanism on each surface is dependent on the cell operating potential, as increasing the potential facilitates C–H bond scission, in turn promoting the formation of intermediates for which C–O scission is more facile. We additionally demonstrate that CO oxidation determines the high overpotential required for electro-oxidation on Pt surfaces. At practical operating potentials (~0.60 VRHE ), we determine that C–O bond breaking is most likely the most difficult step on all three Pt surfaces studied. Graphical abstract: Highlights: Dimethyl ether electro-oxidation mechanisms are identified from first-principles calculations. CO removal determines the high overpotential required for complete oxidation. The reaction mechanism is both structure sensitive and potential dependent.